Presión de las barras sobre el Congreso en la Nueva Granada en el siglo XIX: ¿una esfera pública plebeya o simplemente “política contenciosa” y expresión de un “repertorio de confrontación”? - Uribe-Uran, Victor M. (Anuario de Historia de América Latina, 2019)
This paper revisits the understanding of the “public sphere” of civil society, including Harbermas’s original formulation and those of various other historians, even Latinamericanists. It argues that it is necessary to supplement some of these views, adding a historical component related to this important concept. It consists of popular political pressure in the form of bodily presence and active participation through shouts, physical gestures toward, and threats directed to state agents. Many of those political expressions regularly targeted deliberating state officials and representatives, in particular legislatures, during critical moments in their functioning. They intended to force members of congress to decide in favor of popular preferences. This would mean that, apart from literary and journalistic production and polemics, intellectual debates and the like, aimed at influencing public policies, a perhaps less glamorous, but quite important and effective expression of popular politics, not precisely a plebeian public sphere, took place in a more informal way. This significant modality, probably better explained through Chares Tilly’s notions of contentious politics and repertories of contention rather than Habermas’s “public sphere”, may have accomplished, in a blunt manner, substantial changes in public policy or in the decisions made by legislators and presumably other state officials. The case of nineteenth-century New Granada congressional politics will serve to illustrate this meaningful historical process.